A randomized controlled trial to prevent excessive gestational weight gain and promote postpartum weight loss in overweight and obese women: Health In Pregnancy and Postpartum (HIPP) - Wilcox, Sara (Contemp Clin Trials, 2018)
BACKGROUND: Interventions to prevent excessive gestational weight gain and promote postpartum weight loss have yielded modest results, particularly in overweight and obese women. OBJECTIVES: To examine the impact of a theory-based lifestyle intervention on gestational weight gain, postpartum weight loss, and related maternal and child outcomes and to examine race differences in these outcomes. DESIGN: A randomized controlled trial (target N=400; 200 intervention, 200 standard care; 200 African American, 200 white). METHODS: Overweight and obese African American and white women ≤16 weeks gestation are recruited from obstetrics and gynecology clinics in South Carolina. Intervention participants receive two in-depth counseling sessions (early pregnancy and postpartum), telephone counseling, behavioral podcasts, and social media support that target weight self-monitoring and increasing physical activity and healthy dietary behavior practices, guided by Social Cognitive Theory. Standard care participants receive monthly mailings and a matched number of podcasts on non-weight related topics. All intervention activities last from ≤18 weeks gestation to 6 months after delivery. Gestational weight gain is the primary outcome. Secondary outcomes are meeting gestational weight gain guidelines (inadequate, adequate, excessive), weekly rate of gestational weight gain, postpartum weight retention, physical activity and dietary behaviors, health-related quality of life, and offspring adiposity. Participants are assessed at baseline (≤16 weeks gestation), 32 weeks gestation, and 6 and 12 months postpartum, and offspring are assessed at 6 and 12 months. SUMMARY: HIPP is an innovative study that addresses significant gaps in the literature. Primary outcome results are expected in 2019.